Effect of Structured Exercise Program and Nutritional Counselling on Fitness in School Children - Kshitija Bansal; Divya Sanghi; Raju K. Parasher; Nitesh Bansal; Barkha Bhatnagar (Physical Treatments, 2025)
Purpose: Childhood and adolescence are important stages of life, as many physical, biological and psychological changes take place during this stage. There are many contributing factors which plays important role during this growing and developmental stages. During these stages, modifiable factors including nutrition and physical fitness are crucial. In order to improve physical fitness, interventions should focus on physical activity, and improving the dietary intake of nutrients. Therefore, the present study aimed to evaluate the impact of nutritional counselling and structured exercise regimen on fitness of elementary school children. Methods: The study included sixty school-age children, ranging between 6-14 years of age who scored poorly on three of the five tests related to the physical fitness. The exclusion criteria consisted of children with recent ligamentous or muscular injury in previous four weeks and were medically instructed not to engage in any of the physical activity. Children were randomly assigned to Group A-structured exercise program (SEP), Group B-nutritional Counselling program (NCP) and Group C-SEP+NCP. Pre-and post-intervention the children were assessed for their fitness parameters like muscle strength, curl up test, flexibility, agility, and cardiovascular endurance. Results: It was observed that fitness of children improved in all groups following four weeks of intervention P<0.05, however the greatest improvements were observed following structured exercises and nutritional counselling (SEP+NCP). Conclusion: There is a definite need to focus on healthy lifestyle in elementary school children which should include both structured exercise and nutritional counselling.